Organic-Transactional Assimilation in a Multicultural Society: Ethnicity, Religion, and Economic Interaction in Kampung 10 Ulu, Indonesia - Samiha, Yulia Tri; Samsudin, Syakirah; Turakhanovn, Abdullayeva Ulfatoy; Hussain, Mohammed (Journal of Malay Islamic Studies, 2026)
Kampung 10 Ulu in Palembang is a multi-ethnic settlement (Malay, Chinese, and Arab) where the community lives harmoniously despite cultural and religious differences. This study aims to analyze the influence of culture and the impact of ethnicity on religious, social, and economic life in the area. Qualitative methods with a naturalistic inquiry approach were used through observation, interviews, and documentation, accompanied by data reduction analysis, data presentation, and verification of findings. The results show that inter-ethnic tolerance is formed through strong interactions, such as the practice of Sanjo (silaturahmi) and cultural adaptations (for example, the Ruwah alms ritual adopted by the Chinese ethnic group). Economically, the strategic location on the banks of the Musi River and the trading habits of the Chinese ethnic group strengthen the trading activities of other communities. Cultural assimilation also occurs through inter-ethnic and inter-religious marriages that do not disrupt family harmony. The findings regarding the concept of 'organic-transactional assimilation' contribute to global multicultural sociology by demonstrating that economic interdependence and shared organic spaces can foster more resilient social integration than formal, top-down models of multiculturalism. The implications of this study confirm that ethnic diversity in Kampung 10 Ulu not only enriches local culture but also creates a model of tolerance and collaboration that can be replicated in other multi-ethnic communities.